2021
DOI: 10.3390/f12121776
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Virtual Nature Therapy on Stress Responses: A Systematic Qualitative Review

Abstract: This study aims to review the key findings of past studies that assessed the impact of virtual environments, such as nature and forests for stress therapy. Previous research has found that virtual reality (VR) experiences affect socio-affective behavior, indicating the potential of using VR for cognitive and psychological stress therapy. However, evidence for the impacts of virtual forest therapy as a stress-reduction technique is lacking, and the usefulness of these techniques has yet to be determined. This r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(17 citation statements)
references
References 57 publications
0
17
0
Order By: Relevance
“…Firstly, due to space limitation, vegetation permeability mentioned in this study only includes the interaction effects of three forest stand attributes (FT, UVC, and UVH) and other forest stand attributes, such as stand density, stand area, and tree height ( 10 , 11 , 17 ), will be explored in the future; secondly, it is time-consuming to manually analyze the 3D vegetation permeability data of 18 VR forest panoramic videos. It is necessary to improve analysis efficiency in the future to reduce the workload of researchers; furthermore, the participants are college students, and although scholars in previous studies have indicated that college students are representative samples ( 49 , 50 ), the demographic characteristics of the participants may influence their perceived preference for the forest stand structure ( 17 , 60 ). For the participants of the present study, the influence of their age, gender, educational back-ground, and major has not been discussed.…”
Section: Discussion and Limitationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Firstly, due to space limitation, vegetation permeability mentioned in this study only includes the interaction effects of three forest stand attributes (FT, UVC, and UVH) and other forest stand attributes, such as stand density, stand area, and tree height ( 10 , 11 , 17 ), will be explored in the future; secondly, it is time-consuming to manually analyze the 3D vegetation permeability data of 18 VR forest panoramic videos. It is necessary to improve analysis efficiency in the future to reduce the workload of researchers; furthermore, the participants are college students, and although scholars in previous studies have indicated that college students are representative samples ( 49 , 50 ), the demographic characteristics of the participants may influence their perceived preference for the forest stand structure ( 17 , 60 ). For the participants of the present study, the influence of their age, gender, educational back-ground, and major has not been discussed.…”
Section: Discussion and Limitationsmentioning
confidence: 99%
“…46 college students participate in the experiment, including 23 males and 23 females, aged between 19 and 27 ( M = 23.33, SD = 1.96). Previous studies have shown that visitors aged between 18 and 35 are the main participants in forest park tourism ( 49 ), and college students are regarded as representative and convenience sample groups in visual stimuli research ( 50 ). All participants are Han people living in Southeast China, and no forestry major student participated for avoiding bias in preferences and perceptions of forests.…”
Section: Methodsmentioning
confidence: 99%
“…Yeo et al ( 87 ) compared the effectiveness of these three virtual nature delivery modes for lowering negative affect and increasing positive affect and found that despite the fact that interactive computer-generated VR provided the highest level of nature connectedness and increase in positive affect, all of the conditions achieved a significant reduction in negative affect that did not differ between the simulation forms. As three-dimensional VR technology becomes prevalent, more research studies have employed VR than have employed 2-D videos as the medium to deliver nature exposure ( 42 , 44 , 88 ). Nonetheless, the potential benefits of a more accessible and generalisable form of virtual nature should not be undervalued when developing stress reduction interventions with clinical implications.…”
Section: Discussionmentioning
confidence: 99%
“…According to recent studies [5], the simulation in Virtual Reality helps patients learn how to cope with their symptoms better and decreases the intensity of the nervous tension. In such a dynamic world, society is increasingly demanding; people are exposed daily to tense circumstances that negatively affect overall mental health, leading to severe disorders and health trouble.…”
Section: List Of Figuresmentioning
confidence: 99%